Physiological profile of elite ice hockey player - Dostal, J.; Matous, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Goal of the study was to set the standard physiological parameters of elite ice hockey player with focus on cardiopulmonary testing. Methodology: 126 elite ice hockey players from NHL, KHL , and ELH (Czech national league) underwent medical examination and cardiopulmonary (VO2max) testing. 15 players out of those 126 were active members of national teams of Czech, Sweden, Finland and Slovakia. All tests were performed in summer 2012 and 2013 at the beginning of the season. The exercise test was performed on bicycle ergometer equipped with Schiller-Ganshorn PowerCube gas analyzer and ECG. The gas analysis averaging time was set for 10 sec. All players performed the spiroergometry test (VO2max) to the maximum exhaustion via ramping protocol with continuous ramp 0,8W/kg/min reaching max oxygen uptake between 6 and 10 min of the load. Results: The following results were recorded ( Mean, SD, Min, Max). Age ( 25.8, 4.9, 18, 39), Height (183, 10, 168, 196), Weight ( 88, 6, 75, 103), Fat % from 10 skinfolds ( 11.2, 3.3, 2.1, 21), Max load W (535, 40, 455, 664), Max load W/kg (6.2, 0.4, 5.0, 7.6), VO2MAX ml/min/kg (53.6, 5.1, 38.4, 62.3), VO2 at ventilatory threshold ml/min/kg (38.1, 4.6, 28.2, 51.8), FVC liter (6.25, 0.8, 4.1, 8,4), FVC % norm (108, 13, 79, 147), Tidal volume at max load liter (3.4, 0.5, 2.2, 4.9), Ventilation in max load liter/min (189, 23, 140, 246), Breathing frequency at max load f/min (57, 9, 38, 83), O2pulse at max load (24.4, 2.7, 17.8, 31.2), Heart rate at rest BPM ( 65, 10.1, 40, 88), Heart rate at ventilatory threshold BPM (165, 9, 140, 190), Heart rate at max load (185, 8.5, 166, 207), Post-exercise lactate at 3-5-10-20min ( 13, 2, 8, 20 - 13, 2, 9, 24 - 12, 2, 8, 17 - 10, 2, 5, 17), Lactate elimination 3min-20min % (26, 13, -15, 52). Discussion: There is very limited amount of valid data on typical physiology profile of cardiopulmonary testing of elite ice hockey players. Our findings on 126 players give the picture of typical profile of elite European ice hockey player. The transfer of those results to the NHL should be taken with caution, as the amount of NHL players in the group was limited (4 players). The mean VO2max is lower than some of the previously published data, most likely due to new technologies used like breathe to breathe gas analyses. The typical profile and distribution is needed to identify individual players with limiting factors, that needs a special training regimen, or in some cases even medical care, mainly in the area of respiratory physiotherapy.